Is there an association between depression and periodontitis? A birth cohort study. (20th January 2019) - Nascimento, Gustavo G.; Gastal, Márcia T.; Leite, Fábio R. M.; Quevedo, Luciana A.; Peres, Karen G.; Peres, Marco A.; Horta, Bernardo L.; Barros, Fernando C.; Demarco, Flávio F.
Abstract: Aim: To investigate the association between depression and periodontitis among adults enrolled in the 1982 Pelotas Birth Cohort, Brazil. Materials and methods: Major depressive episode (MDE) and severity of depressive symptoms obtained in 2012 were considered the exposure of this study. In 2013, periodontitis, the outcome of interest, was clinically assessed and two different case definitions were used: the CDC/AAP and a combination of clinical attachment loss (CAL) and bleeding on probing (BOP) simultaneously. Serum levels of C‐reactive protein and frequency of dental flossing were defined as mediators while confounders comprised a set of variables collected throughout the life‐course of the participants. The parametric g‐formula was used to test the direct, indirect and total effects of depression on periodontitis. Results: 539 participants were clinically examined. Individuals with depressive symptoms presented higher risk of periodontitis (risk ratio [RR] 1.19). The presence of depressive symptoms was also associated with moderate/severe periodontitis (total effect RR 1.18). None of the associations was mediated by flossing or C‐reactive protein levels. Finally, neither the presence of depressive symptoms nor the presence of major depression was associated with the combination of CAL+BOP. Conclusions: A positive association between depressive symptoms and periodontitis and moderate/severe periodontitis was found. MDE was not associated with periodontitis.